Exploring influencing factors to clinical leadership development: a qualitative study with healthcare professionals in Flemish nursing homes - Sabrina Nachtergaele; Nele De Roo; Jolien Allart; Patricia De Vriendt; Mieke Embo; Elise Cornelis (BMC, 2024)
Abstract Background Nursing homes face a critical need for competent healthcare professionals to deliver high-quality care. Focusing on clinical leadership is crucial for equipping healthcare professionals with the skills necessary to manage complex care needs, collaborate effectively within multidisciplinary teams, and improve care quality in nursing homes. Developing clinical leadership fosters professional growth and enhances healthcare professionals' ability to tackle the challenges unique to the nursing home environment. However, the concept of clinical leadership in nursing homes remains poorly defined and investigated. This study aimed to explore and define influencing factors for the development of clinical leadership within healthcare professionals in nursing homes. Methods A qualitative study was conducted in Flanders, Belgium, using semi-structured focus group interviews (n = 5) with healthcare professionals (n = 41), including nurse assistants, licensed practical nurses, registered nurses, occupational therapists, recreational therapists, psychologists, and gerontologists. Interviews were audio-taped, transcribed, analysed and interpretated by using a thematic analysis based on descriptive phenomenology. Results Clinical leadership development within healthcare professionals' hinges on four pivotal themes: (1) Cultivating an empowering working environment that fosters open feedback, encourages peer learning, and champions a stimulating learning climate. (2) Nurturing a supportive leadership style in formal leaders that exemplifies role modeling, accessibility, and a coaching approach. (3) Elevating well-developed professional identity through targeted training, experience, and a talent-oriented work approach. (4) Fostering team dynamics marked by commitment, collaboration, support, and trust. Conclusions The study's findings on the influencing factors for clinical leadership development should be actively applied in nursing homes and guide the creation of targeted training programs and leadership development initiatives. Awareness of these factors are crucial to optimise and to support the development and implementation of clinical leadership in nursing homes in an attempt to reduce the workforce shortages.